Thermal comfort modelling of older people living in care homes: An evaluation of heat balance, adaptive comfort, and thermographic methods. (January 2022) - Yi, Choo yoon; Childs, Charmaine; Peng, Chengzhi; Robinson, Darren
Abstract: Older adults are more thermally vulnerable than the younger adults that comfort metrics tend to be empirically drawn from. They are less able to discriminate between warmth and cold and those that experience motor or neurological impairments may be less able to perceive or communicate their thermal sensation and preference; placing the onus of thermal regulation on their carers. This situation is accentuated as societies age, so that there is a growing need for guidance for the thermal regulation of care homes; to establish whether existing metrics may be used with confidence or whether the evidence base needs to be extended to encompass data from older adults. To this end, this paper presents a study of three approaches to thermal comfort modelling for older age care home residents: (1) Predicted Mean Vote (PMV), (2) Adaptive Comfort, and (3) long wave infrared thermography (IRT). Based on measurements from a previous field survey, our results show that (1) PMV can, in principle, be applicable to older people, but procedures for estimating metabolic rates are outmoded and summertime conditions tend to be free-running; (2) Adaptive Comfort appears to be well suited and can also consider feedback from adaptive actions; (3) The difference in skin temperature obtained from infrared maps of the upper extremities (hands, wrist, forearm) has potential as an indicator of thermal comfort, if these measurements can be practically deployed. However, all three approaches are limited in their ability to account for the distribution of thermal sensations collected from subjects with dementia. Highlights: The potential utilities of three thermal comfort methods/models in care homes are evaluated. PMV can be applicable to care homes in principle but with uncertainties in the data required. Adaptive comfort appears well suited considering clothing changes as adaptive actions in care homes. IRT extremities imaging has potential if it can be practically deployed in care homes. All three approaches are limited to account for the distribution of thermal sensations collected from subjects with dementia.